Analysis of exam questions for the specialization courses of the Faculty of Physical Education and Sports Sciences using Marzano's model of dimensions of learning - Saad, Asst.L. Ahmed Khudair assigned; Badri, Asst.L. Ahmed Tariq (Sulaimani Journal for Humanities, 2025)
The current research aims to analyze the exam questions materials jurisdiction of the College of Physical Education, according to the model Marzano The study found the following results: - Questions that test scores for grades (Alawly- II-Cycle- fourth) have focused on the skill of remembering the first prize, while the comparative skill ranked second and third expansion, as stated in the recent mattresses skill of observation and skill to identify patterns and relationships and skill to identify the main ideas. The researchers concluded that the authors of the final exam questions and focused too heavily on the skills (remember, comparison, expansion) did not respect the balance between the mental capacity to model Marzano to keep learning.
Keywords: Exam questions; Marzuna model; dimensions of learning